2019
DOI: 10.1101/696914
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Hysteresis in the selective synchronization of brain activity to musical rhythm

Abstract: words: 236 Manuscript words: 9488 Significance statementWhen listening to musical rhythm, people tend to spontaneously perceive and move along with a periodic pulse-like meter. Moreover, perception and entrainment to the meter seem to show remarkable stability in the face of dynamically changing rhythmic structure of music. Here we show that this is supported by a selective synchronization of brain activity at meter frequencies. This selective neural synchronization persists longer when a nonrepeating sequence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 91 publications
2
4
0
Order By: Relevance
“…Similar effects of presentation order across the experimental session have been shown for pitch structure in music (Bigand et al, 2003) and metric perception in rhythm (Lenc et al, 2019), and previously heard differences between two sound streams have been shown to influence perception of a subsequent sound stream into one or two streams (e.g., Bregman, 1990;Snyder et al, 2008;Snyder, Holder, Weintraub, Carter, & Alain, 2009). This phenomenon can also be observed in other modalities, notably vision (see Snyder et al, 2015).…”
Section: Response Time (Ms)supporting
confidence: 57%
See 2 more Smart Citations
“…Similar effects of presentation order across the experimental session have been shown for pitch structure in music (Bigand et al, 2003) and metric perception in rhythm (Lenc et al, 2019), and previously heard differences between two sound streams have been shown to influence perception of a subsequent sound stream into one or two streams (e.g., Bregman, 1990;Snyder et al, 2008;Snyder, Holder, Weintraub, Carter, & Alain, 2009). This phenomenon can also be observed in other modalities, notably vision (see Snyder et al, 2015).…”
Section: Response Time (Ms)supporting
confidence: 57%
“…A recent EEG study has also shown a persistence of metrical structure depending on the order rhythms were presented. Rhythms presented in the order of most regular to least regular (ambiguous) resulted in a longer persistence of meter-related neural responses compared to rhythms presented in the order of the least regular to most regular, suggesting a persistence of the initially perceived meter (Lenc et al, 2019).…”
Section: Effects Of Cue Regularity On Subsequent Speech Processingmentioning
confidence: 99%
See 1 more Smart Citation
“…To explore the possibility that 1/3 and 4/3 Hz rhythms were tagged in the EEG, we adopted a previously developed approach that aims at comparing the EEG signal to a processed sound signal modeling cochlear firing patterns ( Lenc et al., 2018 , 2019b ). To this end, we first down-sampled the experimental sound recording for each participant and condition to 5000 Hz.…”
Section: Methodsmentioning
confidence: 99%
“…Recent studies have shown that neuroimaging techniques might offer a particularly promising avenue to explore the spatiotemporal properties of visual periodic motion that are preferentially processed by the brain and used to produce synchronized movements. Indeed, there is growing evidence in the context of auditory–motor synchronization showing that the amplitude of the neural response at the frequency of periodic stimuli measured with EEG during passive listening can predict an individual's capacity to synchronize proficiently with these stimuli (Bouvet et al, 2020; Lenc et al, 2019; Nozaradan et al, 2016). It has been shown that larger EEG responses correlate with better movement synchronization across conditions and participants.…”
Section: Introductionmentioning
confidence: 99%